Indonesian Political Attitude Towards Humanitarian Conflict of Rohingya Ethnic in Myanmar - Fadli Asyhari Lubis (Institute of Computer Science (IOCS), 2020)
This research describes the roots of ethnic conflict in Myanmar and the impact of this conflict. This ethnic conflict involves two ethnicities, namely the Rohingya Muslim ethnicity and the Rakhine Buddhist ethnicity. This conflict causes thousands of people to try to flee every year to Bangladesh, Malaysia and Indonesia. They tried to run away because of their rights which were suppressed because of forced labor and persecution. The root of the problem of this ethnic conflict can be seen from three levels, namely the systemic level which states the attitude of the Myanmar government and the existence of conspiracy with foreign parties, the Domestic level which states the condition of the Myanmar government led by the military junta, and the level of perception which states that Rohingya ethnicities are similar to Bengalis. This conflict caused a massive wave of refugees and humanitarian problems and invited reactions from the international community and the United Nations who have intervened to help resolve ethnic conflicts that have been going on for quite a long time. This study uses a qualitative description research method. Secondary data is obtained through documentary studies, namely through magazines, newspapers, books and other sources related to this research topic.